The surgical strategy for multilevel massive ossification of the posterior longitudinal ligaments - Li, Ying-Ching; Liu, Zhuo-Hao; Li, Ying-Sheng; Yeap, Mun-Chun; Liu, Yu-Tse; Huang, Yin-Cheng; Chen, Ching-Chang; Tu, Po-Hsun (Frontiers in Surgery, 2022)
Purpose: How to make enough decompression, favorable outcome, less complication and maintain adequate lordosis and stability in the patients with cervical myelopathy (CM) due to multilevel massive ossification of the posterior longitudinal ligament (OPLL) still poses a challenge for surgeon. The aim of our study is to retrospectively evaluate our patients and try to seek a better surgical strategy. . Methods: Between 2015 and 2019, 55 consecutive patients with multilevel massive OPLL underwent surgical treatment. Among these cases, 40 patients were treated with cervical laminectomy and then anterior decompression, fusion, and fixation (ADF) which was defined as (Group 1), and 15 patients were treated with cervical laminectomy and fixation simultaneously which was defined as (Group 2). The patient’s radiographic characteristics and postoperative outcomes were evaluated. Results: Better postoperative cervical sagittal lordosis and less long-term axial pain in group 1 (p<0.001), though the functional outcome had no significant difference. In the multivariable analysis, anterior fixation accounts for independent factors for better cervical sagittal alignment. (p<0.001) No complications directedly associated with cervical laminectomy was observed. Conclusion: In the patients with cervical multilevel massive OPLL, laminectomy at compression level and then ADF depended on the severity and range of compression, but corpectomy not more than two vertebral bodies are suggested, except K-line (+) and long-segment massive OPLL majorly involving the C2, posterior laminectomy above and below the OPLL-affected levels with posterior fixation simultaneously.